BASIC PERIODONTAL STATUS AND ORAL HYGIENE PRACTICES AMONG SCHOOL CHILDREN OF HITEC, TAXILA CANTT - Saman Malik; Wajeeha Jabeen; Faiqa Hassan; Usman Ul Haq; Naveed Mazhar Bhatti; Tabassum Naveed (Pakistan Oral & Dental Journal, 2020)
Lack of awareness and knowledge of oral hygiene maintenance are major causes of gingival and periodontal diseases. Maintaining oral hygiene and creating awareness is a major concern in rural areas of Punjab, Pakistan has low educational and health standards.The aim of the study was to assess oral hygiene knowledge and periodontal status in rural areas of Pakistan among students (9 to 11 years having mixed dentition) of HITEC Junior School, Taxila Cantt. A questionnaire was designed by authors and distributed among 200 students (143 males and 57 females). The questionnaire included age, gender, aids of oral hygiene maintenance and frequency of brushing. Student’s oral health status was examined over a period of 10 days using torch as an artificial light source and findings were recorded against bleeding gums, plaque, calculus and pit & fissure caries.Out of 200 students, 190(95%) claimed to brush daily, 117(58.5%) revealed that they brushed once a day, and 55(27.5%) were brushing twice daily. 2(1%) used maswak, 3(1.5%) used their finger for cleaning teeth. Only 5(2.5%) were found not brushing at all and 167(83%) students were using tooth paste on daily basis for brushing, 67(33.5%) knew about the use of mouthwash and out of 200 only 7(3.5%) knew about flossing. In respect to Basic Periodontal Examination (BPE) plaque and calculus was found in 37(18.5%) students. Pit and fissure caries were found in 68(34%) and 132(66%) students had no caries.School going children are more vulnerable to dental diseases, awareness and knowledge in children through school based oral health care educational programs should be increased to decrease the frequency of dental problems.
Keywords: Oral hygiene practices; Basic Periodontal examination; School children